Non-linear associations and threshold effects of BRI, CI, and WHtR with grip strength in U. S. adults aged ≥20 years: a cross-sectional study - Yang, Sijia; Liao, Kun; Zhou, Lu; Zhang, Shengbo; Wu, Jianchao (Frontiers in Nutrition, 2025)
BackgroundMuscle strength is strongly associated with various physiological functions and health risks, with grip strength serving as a key indicator for its assessment. Currently, the relationship between novel obesity indices [Body Roundness Index (BRI), Conicity Index (CI), and waist-to-height ratio (WHtR)] and grip strength remains unclear. The current study aimed to investigate the non-linear/threshold relationships between BRI, CI, WHtR, and grip strength.MethodsA cross-sectional study design was adopted to analyze the data of 9,356 participants from the National Health and Nutrition Examination Survey (NHANES) conducted between 2011 and 2014. Researchers measured grip strength and calculated BRI, CI, and WHtR, while controlling for age, sex, ethnicity, and other covariates. Statistical analyses included linear regression, smooth curve fitting, and threshold effect models to evaluate non-linear/threshold relationships. The significance level was set at a p < 0.05, and 95% confidence intervals (CIs) were reported.ResultsBRI, CI, and WHtR exhibited significant non-linear associations with grip strength. For BRI, values below 3.55 exhibited a strong positive effect on grip strength (β = 3.60, 95% CIs: 2.81–4.39), with weakened but persistent positive effects above this threshold (β = 0.24, 95% CI: 0.10–0.39). WHtR demonstrated a similar pattern, with a threshold set at 0.51: β = 62.46 (48.36–76.55) below and β = 6.47 (2.85–10.08) above. CI showed an inverted U-shaped relationship, shifting from positive (β = 15.87, 7.85–23.90) to negative (β = −9.98, −14.98 to −4.98, p < 0.01) at a threshold of 1.27.ConclusionIn U. S. adults, BRI, CI, and WHtR exhibited non-linear and threshold-dependent associations with grip strength, suggesting that these indices can help refine the assessment of muscle strength. The findings indicate that integrating these indices could enhance the accuracy of risk stratification for muscle dysfunction, particularly in individuals with central obesity. Longitudinal studies are needed to further validate the causal relationships underlying these associations.